Mudanças na comunidade de formigas e na interação formiga-planta durante o desenvolvimento de Caryocar brasiliense (Caryocaraceae) - Koch, Elmo Borges de Azevedo (2014)
Interspecific interactions are one of the main mechanisms that promote and maintain diversity of species in biological communities. The variation in the result of these interactions, also known as \"conditionality\" has been abundantly documented in the ecological literature. Predict the outcome of an interaction and ecological variables governing them, however, is a difficult task. Mutualistic interactions between ants and plants are widely studied, the ants provide various types of services for plants, and among the most common is the protection against herbivores. The aim of this study was to determine whether there is variation in the ant community and in the interaction ant-plant with the development of Caryocar brasiliense. This study was conducted in an area of cerrado sensu stricto in Reserva Ecológica do Panga, located in Uberlândia-MG. I sampled 81 individuals of C. brasiliense, which were separated into three categories related to their stage of development: pre-reproductive, medium-sized reproductive and large-sized reproductive. Tree-dwelling ants were collected using mechanical beating and pitfall-traps containing baits (honey and urine). To determine whether the proportion of ant predation varied with ontogeny, we conducted an experiment, where termites were attached to branches of the plants. To test the effect of the presence of ants on leaf herbivory, leaf shoots with no damage were marked, and half had all ants removed and prevented from returning. After 90 days, leaves were sampled and the herbivory rate was estimated. Additionally, leaves of different stages were sampled to determine the levels of tannins. Were recorded 60 species/morfoespecies of ants distributed in 17 genera and five subfamilies. The ant community composition varied significantly between the developmental stages of C. brasiliense and there was a gradual change in composition as the plant develops. The mean abundance of ants was significantly higher in reproductive plants than in the pre-reproductive ones. The ant species richness also differed with ontogeny, increasing with the development of the plant. I found significant differences on the proportion of predated termites between plants different stages. The experimental exclusion of ants resulted in a significant increase in the amount of herbivory on leaves of C. brasiliense, and this had a positive interaction with the stage of development, being greater in large reproductive plants. Moreover, the total concentration of tannins did not differ between different stages. The degree of protection conferred by the ants depends on the stages of development of C. brasiliensis trees, since large reproductive plants had high rates of predation of termites and higher herbivory rates with the absence of ants. These results provide strong evidence that the ontogeny of the plant is a factor of conditionality in mutualistic interactions between ants and plants.